MAYBE Initial complexity problem: 1: T: (1, 1) f0(a, b, c, d) -> f6(b, b, d, d) (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ 0 >= a + 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ a >= 1 ] (?, 1) f6(a, b, c, d) -> f14(0, b, c, d) [ d >= b + 1 /\ a = 0 ] (?, 1) f6(a, b, c, d) -> f14(0, b, c, d) [ b >= d + 1 /\ a = 0 ] (?, 1) f6(a, b, c, d) -> f14(0, b, c, b) [ a = 0 /\ b = d ] start location: f0 leaf cost: 0 Repeatedly removing leaves of the complexity graph in problem 1 produces the following problem: 2: T: (1, 1) f0(a, b, c, d) -> f6(b, b, d, d) (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ 0 >= a + 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ a >= 1 ] start location: f0 leaf cost: 3 A polynomial rank function with Pol(f0) = 2*V_2 + 1 Pol(f6) = 2*V_1 + 1 orients all transitions weakly and the transition f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ a >= 1 ] strictly and produces the following problem: 3: T: (1, 1) f0(a, b, c, d) -> f6(b, b, d, d) (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ 0 >= a + 1 ] (2*b + 1, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ a >= 1 ] start location: f0 leaf cost: 3 Applied AI with 'oct' on problem 3 to obtain the following invariants: For symbol f6: -X_3 + X_4 >= 0 /\ -X_1 + X_2 >= 0 This yielded the following problem: 4: T: (2*b + 1, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ a >= 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ 0 >= a + 1 ] (1, 1) f0(a, b, c, d) -> f6(b, b, d, d) start location: f0 leaf cost: 3 By chaining the transition f0(a, b, c, d) -> f6(b, b, d, d) with all transitions in problem 4, the following new transitions are obtained: f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ 0 >= b + 1 ] f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ b >= 1 ] We thus obtain the following problem: 5: T: (1, 2) f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ 0 >= b + 1 ] (1, 2) f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ b >= 1 ] (2*b + 1, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ a >= 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ 0 >= a + 1 ] start location: f0 leaf cost: 3 By chaining the transition f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ 0 >= b + 1 ] with all transitions in problem 5, the following new transition is obtained: f0(a, b, c, d) -> f6(b - 2, b, d - 2, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b ] We thus obtain the following problem: 6: T: (1, 3) f0(a, b, c, d) -> f6(b - 2, b, d - 2, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b ] (1, 2) f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ b >= 1 ] (2*b + 1, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ a >= 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ 0 >= a + 1 ] start location: f0 leaf cost: 3 By chaining the transition f0(a, b, c, d) -> f6(b - 2, b, d - 2, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b ] with all transitions in problem 6, the following new transition is obtained: f0(a, b, c, d) -> f6(b - 3, b, d - 3, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 ] We thus obtain the following problem: 7: T: (1, 4) f0(a, b, c, d) -> f6(b - 3, b, d - 3, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 ] (1, 2) f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ b >= 1 ] (2*b + 1, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ a >= 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ 0 >= a + 1 ] start location: f0 leaf cost: 3 By chaining the transition f0(a, b, c, d) -> f6(b - 3, b, d - 3, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 ] with all transitions in problem 7, the following new transition is obtained: f0(a, b, c, d) -> f6(b - 4, b, d - 4, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 ] We thus obtain the following problem: 8: T: (1, 5) f0(a, b, c, d) -> f6(b - 4, b, d - 4, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 ] (1, 2) f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ b >= 1 ] (2*b + 1, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ a >= 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ 0 >= a + 1 ] start location: f0 leaf cost: 3 By chaining the transition f0(a, b, c, d) -> f6(b - 4, b, d - 4, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 ] with all transitions in problem 8, the following new transition is obtained: f0(a, b, c, d) -> f6(b - 5, b, d - 5, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 ] We thus obtain the following problem: 9: T: (1, 6) f0(a, b, c, d) -> f6(b - 5, b, d - 5, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 ] (1, 2) f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ b >= 1 ] (2*b + 1, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ a >= 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ 0 >= a + 1 ] start location: f0 leaf cost: 3 By chaining the transition f0(a, b, c, d) -> f6(b - 5, b, d - 5, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 ] with all transitions in problem 9, the following new transition is obtained: f0(a, b, c, d) -> f6(b - 6, b, d - 6, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 ] We thus obtain the following problem: 10: T: (1, 7) f0(a, b, c, d) -> f6(b - 6, b, d - 6, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 ] (1, 2) f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ b >= 1 ] (2*b + 1, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ a >= 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ 0 >= a + 1 ] start location: f0 leaf cost: 3 By chaining the transition f0(a, b, c, d) -> f6(b - 6, b, d - 6, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 ] with all transitions in problem 10, the following new transition is obtained: f0(a, b, c, d) -> f6(b - 7, b, d - 7, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 ] We thus obtain the following problem: 11: T: (1, 8) f0(a, b, c, d) -> f6(b - 7, b, d - 7, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 ] (1, 2) f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ b >= 1 ] (2*b + 1, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ a >= 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ 0 >= a + 1 ] start location: f0 leaf cost: 3 By chaining the transition f0(a, b, c, d) -> f6(b - 7, b, d - 7, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 ] with all transitions in problem 11, the following new transition is obtained: f0(a, b, c, d) -> f6(b - 8, b, d - 8, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 ] We thus obtain the following problem: 12: T: (1, 9) f0(a, b, c, d) -> f6(b - 8, b, d - 8, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 ] (1, 2) f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ b >= 1 ] (2*b + 1, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ a >= 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ 0 >= a + 1 ] start location: f0 leaf cost: 3 By chaining the transition f0(a, b, c, d) -> f6(b - 8, b, d - 8, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 ] with all transitions in problem 12, the following new transition is obtained: f0(a, b, c, d) -> f6(b - 9, b, d - 9, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 ] We thus obtain the following problem: 13: T: (1, 10) f0(a, b, c, d) -> f6(b - 9, b, d - 9, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 ] (1, 2) f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ b >= 1 ] (2*b + 1, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ a >= 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ 0 >= a + 1 ] start location: f0 leaf cost: 3 By chaining the transition f0(a, b, c, d) -> f6(b - 9, b, d - 9, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 ] with all transitions in problem 13, the following new transition is obtained: f0(a, b, c, d) -> f6(b - 10, b, d - 10, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 /\ 9 >= 0 /\ 0 >= b - 8 ] We thus obtain the following problem: 14: T: (1, 11) f0(a, b, c, d) -> f6(b - 10, b, d - 10, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 /\ 9 >= 0 /\ 0 >= b - 8 ] (1, 2) f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ b >= 1 ] (2*b + 1, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ a >= 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ 0 >= a + 1 ] start location: f0 leaf cost: 3 By chaining the transition f0(a, b, c, d) -> f6(b - 10, b, d - 10, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 /\ 9 >= 0 /\ 0 >= b - 8 ] with all transitions in problem 14, the following new transition is obtained: f0(a, b, c, d) -> f6(b - 11, b, d - 11, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 /\ 9 >= 0 /\ 0 >= b - 8 /\ 10 >= 0 /\ 0 >= b - 9 ] We thus obtain the following problem: 15: T: (1, 12) f0(a, b, c, d) -> f6(b - 11, b, d - 11, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 /\ 9 >= 0 /\ 0 >= b - 8 /\ 10 >= 0 /\ 0 >= b - 9 ] (1, 2) f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ b >= 1 ] (2*b + 1, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ a >= 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ 0 >= a + 1 ] start location: f0 leaf cost: 3 By chaining the transition f0(a, b, c, d) -> f6(b - 11, b, d - 11, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 /\ 9 >= 0 /\ 0 >= b - 8 /\ 10 >= 0 /\ 0 >= b - 9 ] with all transitions in problem 15, the following new transition is obtained: f0(a, b, c, d) -> f6(b - 12, b, d - 12, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 /\ 9 >= 0 /\ 0 >= b - 8 /\ 10 >= 0 /\ 0 >= b - 9 /\ 11 >= 0 /\ 0 >= b - 10 ] We thus obtain the following problem: 16: T: (1, 13) f0(a, b, c, d) -> f6(b - 12, b, d - 12, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 /\ 9 >= 0 /\ 0 >= b - 8 /\ 10 >= 0 /\ 0 >= b - 9 /\ 11 >= 0 /\ 0 >= b - 10 ] (1, 2) f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ b >= 1 ] (2*b + 1, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ a >= 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ 0 >= a + 1 ] start location: f0 leaf cost: 3 By chaining the transition f0(a, b, c, d) -> f6(b - 12, b, d - 12, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 /\ 9 >= 0 /\ 0 >= b - 8 /\ 10 >= 0 /\ 0 >= b - 9 /\ 11 >= 0 /\ 0 >= b - 10 ] with all transitions in problem 16, the following new transition is obtained: f0(a, b, c, d) -> f6(b - 13, b, d - 13, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 /\ 9 >= 0 /\ 0 >= b - 8 /\ 10 >= 0 /\ 0 >= b - 9 /\ 11 >= 0 /\ 0 >= b - 10 /\ 12 >= 0 /\ 0 >= b - 11 ] We thus obtain the following problem: 17: T: (1, 14) f0(a, b, c, d) -> f6(b - 13, b, d - 13, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 /\ 9 >= 0 /\ 0 >= b - 8 /\ 10 >= 0 /\ 0 >= b - 9 /\ 11 >= 0 /\ 0 >= b - 10 /\ 12 >= 0 /\ 0 >= b - 11 ] (1, 2) f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ b >= 1 ] (2*b + 1, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ a >= 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ 0 >= a + 1 ] start location: f0 leaf cost: 3 By chaining the transition f0(a, b, c, d) -> f6(b - 13, b, d - 13, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 /\ 9 >= 0 /\ 0 >= b - 8 /\ 10 >= 0 /\ 0 >= b - 9 /\ 11 >= 0 /\ 0 >= b - 10 /\ 12 >= 0 /\ 0 >= b - 11 ] with all transitions in problem 17, the following new transition is obtained: f0(a, b, c, d) -> f6(b - 14, b, d - 14, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 /\ 9 >= 0 /\ 0 >= b - 8 /\ 10 >= 0 /\ 0 >= b - 9 /\ 11 >= 0 /\ 0 >= b - 10 /\ 12 >= 0 /\ 0 >= b - 11 /\ 13 >= 0 /\ 0 >= b - 12 ] We thus obtain the following problem: 18: T: (1, 15) f0(a, b, c, d) -> f6(b - 14, b, d - 14, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 /\ 9 >= 0 /\ 0 >= b - 8 /\ 10 >= 0 /\ 0 >= b - 9 /\ 11 >= 0 /\ 0 >= b - 10 /\ 12 >= 0 /\ 0 >= b - 11 /\ 13 >= 0 /\ 0 >= b - 12 ] (1, 2) f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ b >= 1 ] (2*b + 1, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ a >= 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ 0 >= a + 1 ] start location: f0 leaf cost: 3 By chaining the transition f0(a, b, c, d) -> f6(b - 14, b, d - 14, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 /\ 9 >= 0 /\ 0 >= b - 8 /\ 10 >= 0 /\ 0 >= b - 9 /\ 11 >= 0 /\ 0 >= b - 10 /\ 12 >= 0 /\ 0 >= b - 11 /\ 13 >= 0 /\ 0 >= b - 12 ] with all transitions in problem 18, the following new transition is obtained: f0(a, b, c, d) -> f6(b - 15, b, d - 15, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 /\ 9 >= 0 /\ 0 >= b - 8 /\ 10 >= 0 /\ 0 >= b - 9 /\ 11 >= 0 /\ 0 >= b - 10 /\ 12 >= 0 /\ 0 >= b - 11 /\ 13 >= 0 /\ 0 >= b - 12 /\ 14 >= 0 /\ 0 >= b - 13 ] We thus obtain the following problem: 19: T: (1, 16) f0(a, b, c, d) -> f6(b - 15, b, d - 15, d) [ 0 >= 0 /\ 0 >= b + 1 /\ 1 >= 0 /\ 0 >= b /\ 2 >= 0 /\ 0 >= b - 1 /\ 3 >= 0 /\ 0 >= b - 2 /\ 4 >= 0 /\ 0 >= b - 3 /\ 5 >= 0 /\ 0 >= b - 4 /\ 6 >= 0 /\ 0 >= b - 5 /\ 7 >= 0 /\ 0 >= b - 6 /\ 8 >= 0 /\ 0 >= b - 7 /\ 9 >= 0 /\ 0 >= b - 8 /\ 10 >= 0 /\ 0 >= b - 9 /\ 11 >= 0 /\ 0 >= b - 10 /\ 12 >= 0 /\ 0 >= b - 11 /\ 13 >= 0 /\ 0 >= b - 12 /\ 14 >= 0 /\ 0 >= b - 13 ] (1, 2) f0(a, b, c, d) -> f6(b - 1, b, d - 1, d) [ 0 >= 0 /\ b >= 1 ] (2*b + 1, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ a >= 1 ] (?, 1) f6(a, b, c, d) -> f6(a - 1, b, c - 1, d) [ -c + d >= 0 /\ -a + b >= 0 /\ 0 >= a + 1 ] start location: f0 leaf cost: 3 Complexity upper bound ? Time: 1.724 sec (SMT: 1.614 sec)